2012
DOI: 10.1016/j.immuni.2012.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase Deregulation in Leukemia and Lymphoma

Abstract: Genetic alterations affecting members of the Janus kinase (JAK) family have been discovered in a wide array of cancers and are particularly prominent in hematological malignancies. In this review, we focus on the role of such lesions in both myeloid and lymphoid tumors. Oncogenic JAK molecules can activate a myriad of canonical downstream signaling pathways as well as directly interact with chromatin in noncanonical processes, the interplay of which results in a plethora of diverse biological consequences. Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
133
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 120 publications
(141 reference statements)
1
133
0
1
Order By: Relevance
“…Recent cancer genome sequencing studies have shown that assorted mutations in JAK1, JAK2, and JAK3 can also induce myeloid neoplasias as well as a smaller number of solid tumors (16,17). Most of these mutations cluster in and around the N-lobe of the pseudokinase domain near the JAK2 V617F mutation, with a smaller subset in the N-lobe of the kinase domain.…”
Section: Jak1 | Jak3mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent cancer genome sequencing studies have shown that assorted mutations in JAK1, JAK2, and JAK3 can also induce myeloid neoplasias as well as a smaller number of solid tumors (16,17). Most of these mutations cluster in and around the N-lobe of the pseudokinase domain near the JAK2 V617F mutation, with a smaller subset in the N-lobe of the kinase domain.…”
Section: Jak1 | Jak3mentioning
confidence: 99%
“…Although JAK kinase inhibition has proven to be an attractive drug target for a number of immune indications (15), the discovery of the JAK2 V617F mutation as causative for polycythemia vera and other myeloproliferative neoplasms (MPNs) has prompted the investigation of all JAK family members in a number of malignancies (16). Recent cancer genome sequencing studies have shown that assorted mutations in JAK1, JAK2, and JAK3 can also induce myeloid neoplasias as well as a smaller number of solid tumors (16,17).…”
Section: Jak1 | Jak3mentioning
confidence: 99%
“…After cytokine binding to these receptors, JAKs undergo tyrosine phosphorylation and initiate the phosphorylation of STAT proteins, which translocate to the nucleus and initiate gene transcription. 8 JAK phosphorylation has also been shown to activate other important pathways such as PI3K, RAS, AKT and MAPK. JAK proteins thus play a pivotal role in many cellular functions such as cell growth, differentiation and survival, and activating mutations of these kinases have been associated with malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…JAK proteins thus play a pivotal role in many cellular functions such as cell growth, differentiation and survival, and activating mutations of these kinases have been associated with malignant transformation. [8][9][10] Since JAK gene silencing had not previously been associated with tumor cell susceptibility to immune attack, we undertook a series of experiments to understand the mechanisms whereby JAK1 and JAK2 modulate tumor susceptibility to NK cells. Because JAK1 and JAK2 signal through the IFNg receptor, we focused on the potential role of IFNg when NK cells interact with tumor cell targets.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic alterations affecting members of the Janus kinases (JAKs) and signal transducers and activators of transcription (STAT) were discovered in a variety of T-cell malignancies (1,2). Furthermore, increases in the common γc cytokine concentrations that signal through the JAK1/3, STAT3/5 pathway have been demonstrated in angioimmunoblastic T-cell lymphoma, gamma delta T-cell lymphoma, and adult T-cell leukemia (ATL), thereby identifying effective therapeutic targets.…”
mentioning
confidence: 99%